Diversity Glass Antennas for Tri-Band WiFi Applications - Peng Fei Hu; Kwok Wa Leung; Kwai Man Luk; Yong Mei Pan; Shao Yong Zheng (Engineering, 2023)
This paper investigates two novel polarization- and pattern-diversity glass dielectric resonator antennas (DRAs), both of which are for tri-band (2.4, 5.2, and 5.8 GHz) wireless fidelity (WiFi) applications. It also investigates what type of diversity antenna is most suitable for WiFi router applications by comparing the two DRAs, along with a new space-diversity glass DRA. These three diversity glass DRAs are also compared with a commercial space-diversity monopole pair to benchmark the performance of the glass DRA in WiFi router applications. In our polarization-diversity antenna, a double-port feeding scheme is developed to excite different DRA modes. The frequencies of the DRA modes are tuned by using a stepped DRA. For the pattern-diversity design, a stacked DRA is introduced to broaden the bandwidth for both the conical and broadside radiation modes. All three of the new diversity antennas were fabricated and measured to verify the simulations. In our experiment, the bit error rate (BER) of the three diversity glass antennas and the reference space-diversity monopole antenna was also measured, and the results are compared and discussed. It is found that the polarization-diversity omnidirectional DRA has the most stable BER among the three.